Deep Learning through Convolutional Neural Networks for Classification of Image: A Novel Approach Using Hyper Filter - Tripathi, Kshitij; Vyas, Rajendra G; Gupta, Anil K (International Journal of Computer Sciences and Engineering, 2019)
The convolutional neural networks (CNN) are artificial neural networks (ANN) having many similarities like layered architecture, neurons, activation function, and learning rate are some of them. There are some differences also like in CNN we can also deal with tensors which is the most distinguishing feature of CNN and these are just multidimensional 2D or 3D arrays. Another difference is layers in CNN are not same as in ANN. The common layers present in CNN are called as convolutional, relu and maxpool and these are generally connected sequentially so that the output of one layer acts as input to another layer. In the current article, the hybrid approach of filters or kernel is proposed and is giving better results in comparison to other kernel initializers like variance scaling normally used in CNN. The dataset used is CIFAR-100.